dcHiC detects differential compartments across multiple Hi-C datasets - Abhijit Chakraborty; Jeffrey G. Wang; Ferhat Ay (Nature Communications, 2022)
The organisation of mammalian genomes plays a role in many biological processes. Here the authors report dcHiC, a tool which uses a multivariate distance measure to identify changes in compartmentalisation among multiple genome-wide chromatin contact maps, and apply this to different human and mouse datasets.